Analisis Kinerja Keuangan Dengan Menggunakan Rasio Likuiditas terhadap Kinerja Organisasi (Jurnal Akuntansi, 2018)
Research Objectives for Analysis of Financial Performance Using Liquidity Ratios on Organizational Performance Case Study at PT JIEP Pulogadung. The method used is the existing financial ratio analysis methods, namely the 2010, 2011, 2012, 2013, 2014, 2014, and 2015 financial statements. By evaluating through the ratio analysis tool, it is expected to be able to know the progress made by management in running the company. The results of the research show that Cash Ratio partially has a positive and significant effect on Organizational Performance. Current Ratio partially has no significant effect on profit studies. Revenue budget and cost budget simultaneously have a significant effect on profit study.